Model of activity of Mayor Aleksey Sokolov and agents stormtroopers under his leadership - Tumavičius, Andrius (Genocidas ir rezistencija, 2018)
In the public narrative on partisan warfare, an extremely important role is played by agents stormtroopers under Mayor Aleksey Sokolov leadership. Many have heard that this person was “the leader of all-Ukrainian agents stormtroopers”, who was sent to Lithuania to organize the activity of agents stormtroopers. Yet, the information known about this person has been scarce so far. By this article it is sought to provide some facts on the biography of A. Sokolov and highlight the principles of activity of special groups under his leadership.A. Sokolov was a specialist in the specific agency-operational area. He was a recipient of various insignia and other honorary awards, which demonstrated appreciation of his activity by the All-Russian Extraordinary Commission (Cheka) authorities. On the other hand, legality of methods used by A. Sokolov and stormtroopers under his leadership raised doubts. It is likely that namely this problem prevented him from awarding the title of the Hero of the Soviet Union.It took to A. Sokolov less than one year of working with the special group in order to create a model of stormtroopers usage adapted to fighting the Ukrainian partisans. In doing this, A. Sokolov consulted the stormtroopers themselves. While being on secondment in Lithuania, he reformed the special group of the Ministry of Internal Affairs (MVD) of Lithuanian Soviet Socialist Republic (LSSR) according to the Ukrainian model. The operation that took place in Grendavė village of Onuškis Rural District in Trakai County was in line with the model of operations carried out in Ukraine: on the basis of operational data, a legend had been created, a list of persons to be detained and interrogated compiled, the stormtroopers, dressed and equipped as the Red Army soldiers, prepared bunkers for future interrogations, wrote minutes containing evidence of the persons detained, etc.A. Sokolov’s expertise and methodical guidance laid the foundation for practical activity of special groups in Lithuania. Further on, the stormtroopers actually employed the tactics, created by A. Sokolov.
Keywords: Lithuania; soviet occupation; repressive structures; agents; repressions